1998
DOI: 10.1074/jbc.273.29.18353
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Molecular Simulation Analysis of Hydrophobic Substrate Recognition by Aminotransferases

Abstract: Aromatic amino acid aminotransferase (AroAT) and aspartate aminotransferase (AspAT) are known as dualsubstrate enzymes, which can bind acidic and hydrophobic substrates in the same pocket (Kawaguchi, S., Nobe, Y., Yasuoka, J., Wakamiya, T., Kusumoto, S., and Kuramitsu, S. (1997) J. Biochem. (Tokyo) 122, 55-63). In order to elucidate the mechanism of hydrophobic substrate recognition, kinetic and thermodynamic analyses using substrates with different hydrophobicities were performed. They revealed that 1) amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…Table 1) of the V2.53L mutation on SNF binding was ϩ 1.66 kcal/mol. Others have measured the contribution of methyl group-methyl group interactions to ligand binding energy, with values ranging from ϩ0.4 kcal/mol to ϩ1.4 kcal/ mol (Bigler et al, 1993;Huang et al, 1995;Morton et al, 1995;Faergeman et al, 1996;Lu et al, 1997;Oue et al, 1997;Kawaguchi and Kuramitsu, 1998). The value calculated from our data (ϩ1.66 kcal/mol) is thus consistent with the loss of a 2.53 methyl group-SNF ␣-methyl group vdW interaction caused by the V2.53L mutation, a prediction of our modeling and MD simulations.…”
Section: Discussionsupporting
confidence: 77%
“…Table 1) of the V2.53L mutation on SNF binding was ϩ 1.66 kcal/mol. Others have measured the contribution of methyl group-methyl group interactions to ligand binding energy, with values ranging from ϩ0.4 kcal/mol to ϩ1.4 kcal/ mol (Bigler et al, 1993;Huang et al, 1995;Morton et al, 1995;Faergeman et al, 1996;Lu et al, 1997;Oue et al, 1997;Kawaguchi and Kuramitsu, 1998). The value calculated from our data (ϩ1.66 kcal/mol) is thus consistent with the loss of a 2.53 methyl group-SNF ␣-methyl group vdW interaction caused by the V2.53L mutation, a prediction of our modeling and MD simulations.…”
Section: Discussionsupporting
confidence: 77%
“…On the basis of these results, the hydrophobicity of the substrate due to the side chain was considered, which is often represented as the partition coefficient (log P) (Finizio et al, 1997). It has also been suggested that the hydrophobicity of the material correlates with biological activities such as: the substrate carbon number and the free energy difference in the reaction (Kawaguchi and Kuramitsu, 1998); the log P n-octanol/water value of the growth inhibitor and microbial activity determined on the basis of cell mass change (Yeom and Daugulis, 1999); and the log P n-octanol/water value and the in vitro apparent permeability (Kristl and Tukker, 1998). In this study, the mechanism of the oil/water two-phase reaction system with DBT monooxygenase activity as the initial reaction was examined using Mycobacterium G3, while considering the hydrophobicity of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…5, open circles) were studied with Cn substrates (12,13). When the free energy difference (⌬G T ‡ ) between the transition state (ES ‡ ) and the unbound enzyme plus the substrate (E ϩ S) (Fig.…”
Section: Comparison Between Crystal and Solution Structures-the Reactmentioning
confidence: 99%
“…3c). )With hydrophobic substrates, it is known that the catalytic efficiency increases in proportion to the side chain length of a series of straight aliphatic substrates (Cn substrates) (12,13). Surprisingly, consecutive additions of a single methylene group to the substrate (from C4 to C7) produce a constant effect on the stabilization energy of the transition state (ES ‡ ) relative to the unbound state (E ϩ S) (Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation